Speculation, Profitability, and Price Stability - Kemp, Murray C. (The Review of Economics and Statistics, 1963)
SPECULATIVE activity may contribute to the stability of price, or it may promote and feed on instability. But how may one determine, for a specific market over a specific period of time, whether on balance the activities of speculators have been stabilizing or destabilizing? It has been maintained by Milton Friedman that destabilizing speculation must be unprofitable since it involves selling at low prices and buying at high prices.' If this proposition were valid, and if it were also true that stabilizing speculation is always profitable (because it involves buying at low prices and selling at high), the question would take a more tractable form. For then the empirical investigators need only identify the sign of speculative profits: if they were positive, the speculators must have contributed to price stability; if profits were negative, speculators must have added to instability. Unfortunately, neither proposition is generally true; counter examples will be produced in sections 2 and 3. They may be untrue, however, only under conditions which in practice are most unlikely to be satisfied. If this were so, speculators' profits might yet serve as a useful, if not infallible, guide to the stabilizing or destabilizing effects of speculators' activities. This possibility is examined in Section 3. In Section 4 there is outlined an alternative, more direct approach to the problem of determining the effects of speculation on stability. It possesses the incidental but substantial advantage of not requiring the direct measurement of speculative profits and losses.